Investigating the Causal Relationship between Poverty and Corruption in the Middle Eastern Countries (Granger-Hsiao, Toda and Yamamoto Causality Approach in Panel Data) - Hadis Piri; Aziz Maraseli (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: The main objective of this paper is to investigate the relationship between poverty and corruption in Middle Eastern countries over the years 1390-1398 using the Granger - Granger causality test, granger and Yamamoto in the panel data.Methodology: The population studied includes countries in the Middle East. Data panels on these countries have been collected from reliable international sources, including the World Bank, and tested using Eviews software. The variables used in this study include comparative poverty, corruption, gross domestic production variables, labour force, inflation rate, unemployment rate, and wage growth rate.Findings: The study results show that the relationship between poverty and corruption in Middle Eastern countries is a one-way causality relationship from poverty to corruption in the Middle Eastern countries, meaning that by increasing poverty, corruption increases. This unilateral causality relationship is confirmed unilateral in both causality approaches.Originality/Value: The study showed that by providing proper training, the government could prevent corruption and increase public awareness by creating educational bases at the level of countries and providing easy access to them for the general public. Then, the government, considering the problems of all classes of people, motivates them to go less towards corruption as much as possible. Also, providing gratuitous assistance to society's weak classes will prevent these problems as much as possible.